Studi Awal Rhodobryum spp. di Sumatera dan Jawa (Koleksi Herbarium Bogoriense) - Ria Windi Lestari (Journal of Biotropical Research and Nature Technology, 2023)
Documentation results of the collection bryophyte in Indonesia that exist in Bogoriense Herbarium is neglected. One of the collections is Rhodobryum tribe from Sumatera and Java. The Rhodobryum is easy to recognize by rosette leaf orientation looks like a rose flower. This genus was observed based on the bryophyte specimens collected in Bogoriense Herbarium. The results were obtained six Rhodobryum species, four of which are previously identification i.e. Rhodobryum russulum, R. giganteum, R.roseum, and R.ontariense. While two of the six unidentification yet i.e. Rhodobryum sp1, and Rhodobryum sp2 that have different characters with four species other.